ANALISIS KEUNTUNGAN PADA INDUSTRI RUMAH TANGGA PENGOLAH IKAN DI KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Nabila Ukhty (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2017)
AbstrakSalting fish is a food a reatively cheap and has good nutritional content. Request Fishevery day and the Vilage of Kuala Bubon Kabupaten Aceh Barat Kecamatan Samatiga is quite higt, many buyers who buy fish to be used as a side dish food suplplement  that  can increase  profits  for  businesses  dried  fish.    This  study  aims  to determine how much cost is issued the pocess of salted fish to the fish processing buiness profit in the District of South Kuala Bubon. This research used primary data obtained from direct interview. Responden were interviewed are entrepreneurs household fish processing industry in the District of South Kuala Bubon with a sample of 30 respondents amounted to the designated purpose. Data analysis techhniques used are qualitative descriptive. Research  findings  indicate  operated processing   home   industry   become   fish   anchovies every month issued a cover fee of Rp.2.617.202 while home industry acceptance emounted Rp.3.953.333. General operating profit home industry of salted fish processing is Rp.1.336.13. Key Word :,Cost, business Profit, home industry salted fish